BILATERAL CHANGES IN UNILATERAL ACHILLES TENDINOPATHY QUANTIFIED USING ULTRASOUND TISSUE CHARACTERISATION. Issue 9 (10th May 2013) - Docking, S I; van Schie, J T M; Daffy, J; Rosengarten, S; Cook, J L
Abstract : Introduction: Achilles tendinopathy is a prevalent musculoskeletal injury in the young athletic population as well as older individuals. A high proportion of individuals develop symptoms within both Achilles tendons as well as an increased incidence of tendon rupture in the contralateral tendon post Achilles tendon rupture. Bilateral pathological changes have been reported in the literature in a number of animal studies, 1 as well as pathological changes observed histologically and ultrasonographically in the asymptomatic tendon.2 3 Recent studies have suggested that these changes may be centrally mediated rather than alterations in gait, and may predispose the tendon to further degeneration and the development of symptoms. The current study examined changes in tendon structure in patients suffering from unilateral Achilles tendinopathy using ultrasound tissue characterisation (UTC) in both the symptomatic and asymptomatic tendon. UTC allows semi quantitative analysis of tendon structure by assessing the stability of the echopattern, which is closely related to the 3-D structure of the tendon. Methods: 13 unilateral Achilles tendinopathy patients were recruited with various times of symptoms. Both Achilles tendons were scanned using UTC. UTC captures 600 contiguous transverse images over a distance of 12 cm and renders a three-dimensional image of the tendon. Tendon structure was quantified from the insertion to the musculotendinous junction using customised software that quantifies the stability of the echopattern and allows semi-quantification of tendon structure, which has previously been matched with pathological specimens. Tendon structure was compared between the symptomatic and asymptomatic tendon using a related-samples Wilcoxon signed rank test. Results: No significant difference was observed for any of the four echo-types between the symptomatic and asymptomatic tendon (p=0.388, p=0.158, 0.624, p=0.824, respectively). Despite no differences being observed in the echopatterns, disorganisation within the asymptomatic group was diffusely scattered throughout the length of the tendon. Disorganisation in the symptomatic tendon was confined to focal lesions predominately characterised by echo-types representing extensive fibrillar disorganisation. Discussion: Despite the overall echopattern of the tendon not differing between the two groups, the distribution of disorganisation within the tendon differed. However, as changes in tendon structure were not confined to the symptomatic tendon, treatments should aim to improve tendon structure in both limbs to minimise the risk of developing symptoms and potential tendon rupture.